The Nexus of Feminine Empowerment and Mythic Revisionism: Contesting Gendered Ontologies within the Contours of Anand Neelakantan’s Ajaya: Roll of the Dice and Rise of Kali - Vijay Karthic R (ILN Journal: Indian Literary Narratives, 2025)
This study critically examines Anand Neelakantan’s Ajaya duology—Ajaya: Roll of the Dice and Rise of Kali—as a transformative mythopoetic retelling of the Mahabharata that foregrounds gendered agency and ethical pluralism. By shifting the narrative perspective to the Kauravas and centering female characters such as Draupadi, Kunti, Gandhari, and Subhadra, Neelakantan challenges traditional binary frameworks of heroism and villainy and destabilizes patriarchal readings of dharma and power. The research explores how women in Ajaya move beyond passive archetypes to become strategic, morally reflective, and psychologically complex agents who shape the epic’s social, political, and ethical dynamics. Through nuanced characterization, multi-focal narrative strategies, and a critique of caste and patriarchal hierarchies, the duology offers new interpretive possibilities for the Mahabharata, demonstrating that female perspectives are indispensable to the understanding of justice, morality, and agency within epic literature. Ultimately, the study argues that Neelakantan’s work not only restores marginalized voices but also provides a compelling template for critically reimagining classical texts in ways that promote ethical sophistication and narrative inclusivity.